2009
DOI: 10.1038/sj.bjc.6604952
|View full text |Cite
|
Sign up to set email alerts
|

Hospital anxiety and depression scale cutoff scores for cancer patients in acute care

Abstract: The aim of this study was to determine optimal cutoff scores for the Hospital Anxiety and Depression Scale (HADS) when used in evaluating cancer patients in acute care. A total of 689 cancer patients were assessed during their first days of in-patient treatment, using the structured clinical interview for DSM and the HADS. Statistical analysis was performed using ROC curves. A total of 222 patients (32%) had a mental disorder. The area under the curve was the best in the total scale of the HADS, namely 0.73. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
210
1
12

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(229 citation statements)
references
References 28 publications
6
210
1
12
Order By: Relevance
“…However, when screening for depression in cancer patients, studies suggest that the HADS-D should be used with caution due to the variability in optimal cut-off scores [12]. Although not recommended by the original authors, HADS-A and HADS-D can be combined to produce a total score (HADS-T), used as a screen for general psychological distress [13][14][15]. Ravazi et al suggested that a score[13 is an appropriate cut-off to screen specifically for adjustment disorders and major depressive disorders in cancer in-patients.…”
Section: The Hadsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when screening for depression in cancer patients, studies suggest that the HADS-D should be used with caution due to the variability in optimal cut-off scores [12]. Although not recommended by the original authors, HADS-A and HADS-D can be combined to produce a total score (HADS-T), used as a screen for general psychological distress [13][14][15]. Ravazi et al suggested that a score[13 is an appropriate cut-off to screen specifically for adjustment disorders and major depressive disorders in cancer in-patients.…”
Section: The Hadsmentioning
confidence: 99%
“…Ravazi et al suggested that a score[13 is an appropriate cut-off to screen specifically for adjustment disorders and major depressive disorders in cancer in-patients. A more recent study suggests that a cut-off [12 offers optimal sensitivity and specificity in screening for all types of psychological distress in cancer in-patients [15]. We are not aware of studies validating HADS-T cut-off scores for psychological distress in disease-free cancer survivors.…”
Section: The Hadsmentioning
confidence: 99%
“…Durante el proceso oncológico principalmente en el periodo de tratamiento, la presencia de depresión constituye una constante en la vida del paciente con cán-cer (11,12,35) .…”
Section: Depresiónunclassified
“…La presencia de ansiedad y depresión en el paciente con CT se encuentran asociadas con la edad joven, la nuliparidad, la neuropatía periférica, el desempleo, los problemas económicos, problemas por el consumo excesivo de alcohol, problemas sexuales y haber sido tratados por problemas de salud mental previamente (9)(10) . En el paciente oncológico ambas patología psicológicas pueden afectar la evolución de la enfermedad, tratamiento y pronóstico, puesto que tienen como consecuencia un menor nivel de adherencia terapéutica y calidad de vida; incluso persistiendo después de que se ha completado el tratamiento (3,11,12) . En este contexto el tipo de afrontamiento que adopte el paciente ante el cáncer y su tratamiento puede representar un mecanismo adaptativo, y en sentido contrario una mayor disfuncionalidad (13,14) .…”
Section: Introductionunclassified
“…The subjects who have scores of at least 1 on VAS were considered as with pain (n=58). Turkish version (18) of Hospital Anxiety and Depression Scale (HADS), the most widely used tool for assessing psychological morbidity in cancer patients was administered to measure the severity of anxiety and depression (19,20). HADS consists of 14 brief items divided into two subscales designed to screen for anxiety and depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%